Volt-ampere characteristics of porcine retinal Muller cell intermediate filaments - Makarov, Vladimir (2021)
In the current study we reported current-voltage (I/V) characteristics of Muller cell (MC) intermediate filaments (IFs) isolated from porcine retina. It was found that the measured I/V dependences demonstrate behavior of a semiconductor in contact with metal (Au) electrodes. The analysis of the temperature dependence of the experimental I/V curves produced estimates of the parameter values characterizing the electrical conductivity properties of the studied MC IFs. The I/V characteristics and the parameter values allowed to describe the MC IFs as a semiconducting material. The observed properties clarify the mechanism of high-contrast daylight vision of vertebrate eyes. This mechanism was extensively discussed earlier, and is directly dependent on the electric conductivity properties of MC IFs. Significance Statement: Retinal cones and rods are physically connected to glial Muller cells by intermediate filaments (IFs). Electric conductivity of IFs allows for a simple quantum mechanical description of light energy transmission through the retina, providing a convincing mechanism that achieves high-contrast vision in vertebrate eyes. Note that classic light transmission is hindered by light scattering on the retinal structures. Electric conductivity of IFs also opens the possibility for energy exchange within and between other cell types by way of IFs and microtubules, and the possibility that such structures may be used for signaling e.g. in the nervous system.